Prarancangan Pabrik Hexamine Dari Amonia Dan Formalin Dengan Proses Leonard Kapasitas 45.000 Ton/Tahun - Hussen, Utsman Faisal; , Hamid Abdillah, S.T., M.T; , Ir. Herry Purnama, M.T., Ph.D (2017)
Hexamine is useful raw materials, such as explosive, antiseptics in medicine, anti-corrosion material in metal industry, absorbent material for poisonous gas, anti-caking agent in industry of urea fertilizer, additives in resin industry, accelerator in rubber industry, shrink-proofing agent in textile industry, additives in manufacture of cellulose fibers, and fungicide in food industry for fruits. The Plant of hexamine made of formalin and ammonia by the Leonard process of 45.000 ton/year is planned to operate in 330 days in a year. 3:2 is used as the ratio of mol formalin: ammonia used in Hexamine production process. The reaction is done in continous stirred tank reactor which in the phase of liquid-liquid, irreversible and exothermic in the temperature of 38oC and the pressure of 16 atm. In this plant, the need of formalin is 160.704,67ton/year, and the need of ammonia is 22.467,43ton/year. The product of hexamine is 45.000 ton/year. Proponent utilities for the process are 75.027,16kg/hour of water supply gotten from the river, 185.326,41kg/hour 185.326,41kg/hour of the steam need gotten from boiler, 101,52m3/hour of the pressed-air need, 386,10 kW of the electricity need gotten from: 77,22 kW of PLN and 308,88 kW of generator, and 1019,55 L/hour of the diesel fuel need. This plant is built in Kawasan Industri Kujang Cikampek (KIKC), West-Java by the area of 40.972 m2 and 168 employees. The type of the plant is Perseroan Terbatas (PT). The systems used in this plant are shift and non-shift working time. This hexamine plant use Rp360.217.310.445,00 as fixed capital and Rp96.072.005.457,00 as working capital. The economic analysis results of this plant show the profit each year as much as: Rp99.318.004.275,00 (before tax) and Rp69.522.602.993,00 (after tax), Return On Investment (ROI) as much as: 27,57% (before tax) and 19,30% (after tax), Pay Out Time (POT) as long as: 2,6 years (before tax) and 3,4 (after tax), Break Even Point (BEP) as much as 46,76%, Shut Down Point (SDP) as much as 22,91%, and Internal Rate Return (IRR) based on Discounted Cash Flow (DCF) as much as 37,81%. From the data analysis above we can conclude that this plant is profitable and reasonable to build. Keywords:hexamine, continous stirred tank reactor, reasonable